Du mythe de l’efficience des marchés au krach - David Bourghelle; Pauline Hyme (Revue de la Régulation)
For most analysts, the main outward sign of the financial crisis which began in early 2007 is the sudden disappearance of the market values of securitized assets and credit derivatives. This diagnosis naturally suggests some reforms which aim to secure market liquidity. Among them, a flagship measure considered during the last few months is to standardize asset backed securities so as to encourage increased trading in the secondary market. This proposal is intended to reinforce market transparency, provide a market price for risk and to reduce asymmetric information which is identified as the main cause of the liquidity drop. Two theoretical arguments can be put forward to support the promotion of organized Exchanges. First, assets negotiability would reduce the return required by investors and so the cost of capital, second, it would facilitate informational efficiency. Nevertheless, a deeper analysis reveals the dark side of market liquidity. The main purpose of this paper is to show that market liquidity observed on organized Exchanges not only prevents market prices from being efficient but it also generates attraction for speculative trading. It leads to profound changes in agent’s rationality. Far from favouring a fundamentals-based rationality, where every participant of the market seeks to estimate the objective value of assets by rationally calculate the discounted stream of future expected rewards and risks, market prices and, more generally, the agents ability to resell assets, completely dominate the traders’ mindset and compel them to adopt a self-referential rationality. This kind of rationality is entirely directed toward the prediction of what the dominant opinion of the market, in the form of the price, will be. Consequently, the market price stems from an endogenous product of the market itself. By subjecting asset valuation to an instantaneous collective assessment, market liquidity converts asset pricing into an unstable process. Moreover, the collective exit door from markets is closed off during market liquidity runs at the very moment when it is most needed. Would the loss of sense, collective standards and clear-sightedness be the high price to pay for getting liquid markets? Such is the liquidity dilemma that Keynes stressed seventy years ago.